2-Deoxy-D-glucose suppresses the migration and reverses the drug resistance of colon cancer cells through ADAM expression regulation. Issue 4 (April 2017) - Park, Ga B.; Chung, Yoon H.; Kim, Daejin
Abstract : Cancer cell resistance to chemotherapy is associated with a poor prognosis. The compound 2-deoxy-D-glucose (2-DG) enhances the effect of chemotherapy against cancer cells lines in vitro and in vivo . However, its effect on the epithelial to mesenchymal transition (EMT) in drug-resistant cancer cells has not been fully elucidated. In this study, we investigated whether treatment of 5-fluorouracil or oxaliplatin-resistant colorectal cancer (CRC) cells with 2-DG suppressed their migratory activity and enhanced their susceptibility to chemotherapy. Chemoresistant CRC cells stably expressed drug resistance-related proteins (MDR1, MRP1, MRP2, and MRP3) and showed mesenchymal characteristics and a migratory phenotype. 2-DG treatment attenuated glycolysis-related enzyme expression, invasion activity, and EMT-related cytokine secretion in drug-resistant CRC cells. In addition, 2-DG inhibited the activation of a disintegrin and metalloproteinase 10 (ADAM10) and ADAM17. Gene silencing of ADAM10 and ADAM17 with small interfering RNA downregulated mesenchymal properties, reduced EMT-associated cytokine secretion, and rendered chemoresistant cells susceptible to anticancer drug treatment. Collectively, these findings suggest that increased glycolytic metabolism in drug-resistant cells has an effect on both migratory activity and cell viability through the activation of ADAM10 and ADAM17. Abstract : Supplemental Digital Content is available in the text.